Rearrangements of Nitrile-Stabilized Ammonium Ylides - Lahm, Günther; Orejarena Pacheco, Julio Cesar; Opatz, Till (Synthesis, 2014)
Rearrangements of nitrile-stabilized ammonium ylides are useful reactions for the construction of alkylamines, nitrogen heterocycles, or carbonyl compounds. In spite of their attractive synthetic potential, they are much less frequently used than rearrangements of ammonium ylides either carrying charge-stabilizing carbonyl groups or being devoid of additional stabilization of the negative charge. This review focuses on different classes of rearrangements of nitrile-stabilized ammonium ylides as well as their application in synthetic organic chemistry.1 Introduction2 [1,2]-Stevens Rearrangements 3 [2,3]-Sommelet–Hauser Rearrangement4 [2,3]-Stevens Rearrangements5 Competitive [1,2]-, [2,3]-, and [1,4]-Rearrangements6 [1,4]-Rearrangements Involving Ring Expansion7 Summary
Keywords: ylides; rearrangement; ring expansion; amines; heterocycles